Suburban Office Building: Austin, Texas (Oz, 1988)
Located west of downtown Austin, Texas, at the edge of a rapidly developing suburban neighborhood, the 6.8-acre site is near the intersection of the high speed artery Mo Pac Boulevard and Texas Highway 2222…